Inovasi Layanan One Day Service pada Pelayanan Online Single Submission (OSS) di Mal Pelayanan Publik Kabupaten Kediri - Iqbal Athalla Hardito; Eva Hany Fanida (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe and analyze the implementation of the One Day Service innovation in the Online Single Submission (OSS) system at the Public Service Mall (MPP) of Kediri Regency. A descriptive qualitative approach was employed to evaluate the implementation based on the four dimensions of electronic service quality (E-ServQual): efficiency, fulfillment, system availability, and privacy. The findings indicate that, administratively, the efficiency dimension has been systematically designed through a simplified service procedure. However, the regulatory transition following Government Regulation Number 28 of 2025 created systemic obstacles during implementation. The failure of automatic synchronization of the Indonesian Standard Industrial Classification (KBLI) codes hindered the fulfillment of the one-day service commitment and reduced the system availability of the OSS platform. Weaknesses in the central infrastructure were addressed by the local government through communication mitigation strategies and the provision of the KESATU local application as a supporting service facility. Regarding the privacy dimension, the study identified a trust paradox, in which service users placed greater trust in the integrity of front-line officers than in the security reliability of the OSS digital platform. These findings indicate that stronger intergovernmental system integration is required before new regulations are fully implemented.